Synthesis of high molecular weight DNA ladder / Dayana Abdul Bari - Abdul Bari, Dayana (2009)
DNA ladder has been used as a tool in laboratories to determine the size of DNA fragment. The aim of this study is to synthesize high molecular weight DNA ladder and to optimize PCR reaction in order to obtain high yield and specific product. High molecular weight DNA ladder ranges from 0.5 - 10 kbp. DNA ladder is synthesized by using Polymerase Chain Reaction (PCR) method, where lambda phage DNA is used as a template for both PCR reaction and designing primer. The results showed that high molecular weight DNA ladder could be synthesized in laboratory setup. Thus, it could be used as a laboratory tool in the future and may reduce the cost incurred by the faculty in carrying out related studies.